Digital Parenting as A Predictor of Second Language Acquisition in Children - Lucky Ade Sessiani; Alya Lupita Dewanti; Anisatun Niswah (Psikostudia : Jurnal Psikologi, 2025)
Technology access and digital media exposure allows children to develop skills using a second or foreign language. On the other hand, as part of children's daily lives, parents need digital parenting to ensure the benefits of technology and digital media for children's development. This study aims to empirically test the role of digital parenting in determining second language acquisition in children. A total of 175 parents with children aged 4-9 years were involved in this research. Convenience sampling was carried out by distributing research instruments to the parent community of kindergarten and elementary school students. Simple linear regression statistical analysis shows a significance level of 0.000 (p